Applications of multi-component condensations and development of polyamine synthesis on solid-phase - Jönsson, Daniel, 1973-
Solid-phase synthesis of small non-polymeric molecules has become increasingly important as a tool in the development of pharmacologically active compounds. Of particular interest are the syntheses of compounds with low molecular weight, low polarity and a reduced flexibility of the functional groups, i.e. physiochemical properties typical for the majority of drugs currently in use. The first part of this thesis describes the synthesis of polycyclic structures with constrained conformation, by the application of multi-component condensations on solid-phase. The 8-azabicyclo[3.2.1]octan-3-one structure of the tropane alkaloids was synthesized on solid-phase by a modification of the well known Robinson tropinone synthesis. The 3-component reaction was performed with the amino component anchored to a solid support, consisting of polyethyleneglycol-grafted polystyrene. Treatment of the primary amine with 1,3-acetonedicarboxylic acid and excess of succinaldehyde, resulted in high purity of the corresponding tropane derivative. Further derivatization of the resin-bound tropane derivative was performed by reduction of the keto-group and acylation of the hydroxyl-group. The oxygen-bridged tetrahydropyridones are relatively complex polycyclic structures, which previously have been synthesized in solution by condensation of primary amines, coumarin-3-carboxylic acid and ketones. In the evaluation of a solid-phase approach of this 3-component condensation, several members of this class of compounds were synthesized with the amine anchored to a solid support. The yield and purity of the products were dependent on the ketones used in the reaction, but the expected products were obtained using both acyclic and cyclic ketones and substituted acetophenones. The second part of this thesis describes the development of a solid-phase polyamine synthesis. The polyamines are a class of compounds with a wide range of pharmacological and physiological effects, which are constituents in man